Diagnostic tests for SARS-CoV-2: current status and issues - Mazumder, Sraboni; Hoque, Md Monirul (IMC Journal of Medical Science, 2021)
The current coronavirus disease 2019 (COVID-19) pandemic has affected the whole world. Accurate, rapid and affordable diagnostic testing for COVID-19 is crucial to prevent and control this global pandemic. This paper reviews the current status and issues related to diagnostic tests for COVID-19. Ibrahim Med. Coll. J. 2020; 14(2): 60-66